1970
DOI: 10.1017/s0007485300040748
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft applications of insecticides in East Africa. XIX. A comparison of two sampling techniques for assessing the effectiveness of pyrethrum applications on Glossina pallidipes Aust.

Abstract: IntroductionThis paper briefly describes an experiment in the Lossitete Forest area of northern Tanzania (Irving et al., 1969) to compare the fly-round and Langridge-trap techniques of assessing populations of Glossina pallidipes Aust. before and after treatment of the area with pyrethrum from the air. The experiment was carried out in 1968 using aerial-spraying techniques previously described by Irving et al. (1969). Three spray applications were completed. In applications 1 and 2 an oil solution of 25% pyret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1973
1973
1982
1982

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…failed to achieve eradication of G. pallidipes after six treatments of pyrethrum synergised with piperonyl butoxide. Marked reduction of the population was achieved but there is some doubt as to the precise extent of this reduction (Tarimo et al, 1970). Reduction of tsetse populations by aerial application of pyrethrum merits further study.…”
Section: Application Of Insecticides From the Airmentioning
confidence: 98%
See 1 more Smart Citation
“…failed to achieve eradication of G. pallidipes after six treatments of pyrethrum synergised with piperonyl butoxide. Marked reduction of the population was achieved but there is some doubt as to the precise extent of this reduction (Tarimo et al, 1970). Reduction of tsetse populations by aerial application of pyrethrum merits further study.…”
Section: Application Of Insecticides From the Airmentioning
confidence: 98%
“…The difficulty of detecting ultralow-density populations of Glossina has already been discussed (p. 364) but even degrees of reduction short of eradication are difficult to quantify. Tarimo et al (1970) made three applications of pyrethrum by air to a population of G. pallidipes; whereas fly round samples suggested reduction of the population by 64%, 36% and 29% after the three applications, catches from 12 Langridge traps suggested that the population had been reduced by 11%, 7% and 0%,. Which, if either, of these two quite different assessments was correct?…”
Section: Fluctuations In Numbersmentioning
confidence: 98%